Optimalisasi Pengelolaan Keuangan UMKM Jamil Donuts melalui Pembukuan Sederhana Berbasis Microsoft Excel di Desa Kota Guring - Firmansyah F; Winda Rika Lestari (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy but still face challenges in financial management, particularly in maintaining systematic financial records. This issue is experienced by Jamil Donuts MSME in Kota Guring Village, which lacks structured bookkeeping and still mixes personal and business finances. This community service activity aims to optimize financial management through the implementation of simple bookkeeping based on Microsoft Excel. The method used is a participatory approach involving observation, training, mentoring, and evaluation. The results show an improvement in the owner’s understanding and skills in recording financial transactions, preparing simple financial reports, and using Microsoft Excel. In addition, financial records become more organized, systematic, and easier to monitor. Therefore, this activity effectively improves MSME financial management capabilities and supports better business decision-making.